Implementasi Konsep Ekonomi Sirkular Di Masyarakat Sekitar Hutan Melalui Pelatihan Pembuatan Pupuk Organik Berbahan Baku Kotoran Ternak - Budiyoko Budiyoko; Sunendar Sunendar; Lutfi Zukkifli; Malinda Aptika Rachmah; Budi Dharmawan; Dewanti Risa Utami; Wahyu Adhi Saputro; Kunandar Prasetyo; Muhammad Bachtiar Musthafa (Universitas Maritim AMNI Semarang, 2024)
The sustainability of the forest ecosystem is threatened by increased human activities and anthropogenic factors. This condition can have implications for the sustainability of communities around the forest. This community service activity aims to implement the circular economy concept through training in the production of organic fertilizer from livestock manure in Kemutug Lor Village, Baturraden District, Banyumas Regency. The beneficiaries of this activity are community groups around the forest affiliated with the LMDH Wana Karya Lestari. The community service is conducted through a participatory learning and action approach, aiming to enhance community participation in developing knowledge and practical skills related to the utilization of waste as a sustainable resource. The training process includes theoretical presentations, practical fertilizer production, and application to plants. This activity is expected to increase awareness and skills among the community in converting livestock manure into organic fertilizer and developing a sustainable local economy.